2004
DOI: 10.1007/s10600-005-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

Diastereotopic synthesis of 1- and 1,1-substituted 4-phenyl-2,3,4,9-tetrahydro-1H-β-carbolines

Abstract: 547.759.3 V. N. Azev, 2 and V. V. Kachala 3A diastereotopic Pictet-Spengler reaction was performed to form previously unknown 1-and 1,1-substituted 4-phenyl-β-carbolines based on β-phenyltryptamine, aldehydes of various structure, and isatins. It has been demonstrated that the predominant diastereomers of the prepared β-carbolines have the (R*,R*) configuration. The diasteroselectivity (de) of the reaction varies from 44 to 88%.The Pictet-Spengler reaction, which occurs in plants and in humans, leads to the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…3-(2-Nitro-1-phenylethyl)-1H-indole [7] (26.6 g, 0.1 mol) dissolved in alcohol (94%, 100 mL) and freshly prepared Raney nickel (1 g) were boiled, treated with hydrazine hydrate (1 mol) in alcohol (94%, 100 mL), and boiled for 60 h. If the boiling stopped, a new portion of catalyst was added. The solution was filtered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-(2-Nitro-1-phenylethyl)-1H-indole [7] (26.6 g, 0.1 mol) dissolved in alcohol (94%, 100 mL) and freshly prepared Raney nickel (1 g) were boiled, treated with hydrazine hydrate (1 mol) in alcohol (94%, 100 mL), and boiled for 60 h. If the boiling stopped, a new portion of catalyst was added. The solution was filtered.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that the Pictet-Spengler reaction can be made diastereospecific by using β-phenyltryptamine (1) and various carbonyl compounds as starting materials [7][8][9][10][11]. Herein the possibility of forming and preparing a diastereomeric excess of (1R * ,4R * )-4-phenyl-1-(2-thienyl)-2,3,4,9-tetrahydro-1H-β-carboline using the Pictet-Spengler reaction and β-phenyltryptamine (1) and 2-thiophenecarbaldehyde (2) as starting materials was studied [12].…”
Section: And V N Azevmentioning
confidence: 99%
“…Unless otherwise stated, all reagents were purchased from commercial suppliers and used as received. 5,7-Dibromoisatin 15 and 5,7-dichloroisatin 16 were prepared by halogenation of isatin with bromine and isocyanuric chloride, respectively. Isatoic anhydrides 1a-d were synthesized by oxidation of corresponding isatins with H 2 O 2 in glacial AcOH.…”
Section: Paper Synthesismentioning
confidence: 99%
“…Altogether, this plant with possible reduction of blood pressure and enhancing the recovery of I/R can be a good choice in cardiac diseases but more studies needed. 37,91 ROS production is one of the main mechanisms of myocardial dysfunction and necrosis after I/R. superoxide dismutase (SOD) enzymes can control the radical species or ROS in myocardium.…”
Section: Experimental and Clinical Studiesmentioning
confidence: 99%